2020
DOI: 10.1038/s41416-020-0887-6
|View full text |Cite
|
Sign up to set email alerts
|

UGT2B17 modifies drug response in chronic lymphocytic leukaemia

Abstract: Background High UGT2B17 is associated with poor prognosis in untreated chronic lymphocytic leukaemia (CLL) patients and its expression is induced in non-responders to fludarabine-containing regimens. We examined whether UGT2B17, the predominant lymphoid glucuronosyltransferase, affects leukaemic drug response and is involved in the metabolic inactivation of anti-leukaemic agents. Methods Functional enzymatic assays and patients’ plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…Moreover, our observed associations of intratumoral UGT expression with patient survival highlight their potential as prognostic biomarkers. In addition to the data shown here that assessed OS within 33 TCGA cancer types, other studies have reported the prognostic value of various UGTs in specific subsets of cancer patients [6,38,39,75]. For example, previous work shows that UGT2B17 and UGT2B28 are overexpressed in advanced and metastatic prostate cancer and associate with poor outcomes [6,[81][82][83].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Moreover, our observed associations of intratumoral UGT expression with patient survival highlight their potential as prognostic biomarkers. In addition to the data shown here that assessed OS within 33 TCGA cancer types, other studies have reported the prognostic value of various UGTs in specific subsets of cancer patients [6,38,39,75]. For example, previous work shows that UGT2B17 and UGT2B28 are overexpressed in advanced and metastatic prostate cancer and associate with poor outcomes [6,[81][82][83].…”
Section: Discussionmentioning
confidence: 57%
“…The expression and activity of UGT genes within the tumor may also impact cancer development and progression through intratumoral inactivation of carcinogens and anticancer drugs. For example, high UGT2B17 expression has recently been shown to be associated with poor prognosis in chronic lymphocytic leukaemia (CLL), partly due to enhanced local inactivation of anti-leukaemic drugs (e.g., fludarabine) within CLL cells [38,39]. Therefore, it is necessary to systematically assess whether the intratumoral expression of UGT genes could be associated with clinical outcomes in different human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several specific UGTs emerge as prognostic markers in multiple cancer types (leukemia, lung, prostate, colon, breast, bladder, etc.) and as predictive markers of drug responses, including in treatment-naïve patients [ 3 , 14 , 21 , 25 , 28 , 29 , 30 , 31 , 32 ]. However, the impact of UGT enzymes and alt.…”
Section: Introductionmentioning
confidence: 99%
“… 7 All UGTs are known for their high interindividual variation based on copy number variations, polymorphisms, and drug-induced expression, and, in addition, seem to be governed by alternative and/or additional forms of regulation. 99 Recently, it was shown that several of these enzymes were induced upon drug incubation of CLL cells in vitro leading to increased glucuronidation and inactivation of drugs, which included both chemotherapeutic and targeting agents. 99 The clinical consequences still have to be studied.…”
mentioning
confidence: 99%
“… 99 Recently, it was shown that several of these enzymes were induced upon drug incubation of CLL cells in vitro leading to increased glucuronidation and inactivation of drugs, which included both chemotherapeutic and targeting agents. 99 The clinical consequences still have to be studied.…”
mentioning
confidence: 99%